2013
DOI: 10.1159/000355241
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of Double-Filtration Plasmapheresis plus Interferon Treatment in Nonresponders to Pegylated Interferon plus Ribavirin Combination Therapy

Abstract: Objectives: We assessed the outcome of double-filtration plasmapheresis (DFPP) combined with pegylated interferon (PEG-IFN) and ribavirin (RBV) therapy in patients infected with hepatitis C virus (HCV)-1b whose HCV had not disappeared during PEG-IFN/RBV combination therapy, or who had relapsed after the end of the therapy. Additionally, we investigated factors predictive of sustained virological response (SVR), including host and viral genetic factors, to DFPP plus IFN/RBV therapy. Methods: A total of 40 patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…One hundred and seventy patients with HCV‐related liver disease were transplanted in our center between 2005 and 2013. Thirteen Caucasian patients (48 years [45–62], 11 males) presenting a diagnosis of fibrosing cholestatic hepatitis ( N = 8) or severe conventional HCV recurrence ( N = 5, HVPG: 11.5 mm Hg ) were enrolled into the MARS salvage protocol (Table ). They had similar demographic and laboratory characteristics at baseline (Supplementary Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…One hundred and seventy patients with HCV‐related liver disease were transplanted in our center between 2005 and 2013. Thirteen Caucasian patients (48 years [45–62], 11 males) presenting a diagnosis of fibrosing cholestatic hepatitis ( N = 8) or severe conventional HCV recurrence ( N = 5, HVPG: 11.5 mm Hg ) were enrolled into the MARS salvage protocol (Table ). They had similar demographic and laboratory characteristics at baseline (Supplementary Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Patients received the MARS treatment at a median of 3 months after LT. Two patients with HCV viral load above the upper limit of detection before and after MARS treatment were excluded from the analysis of viral kinetics. The 3‐day MARS treatment induced decreases of HCV viral load in all the remaining patients (7.59 log 10 IU/mL [6.15–8.90] to 6.79 log 10 IU/mL [5.18–7.84], P = 0.003, Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients who underwent the prophylactic combination treatment of low-dose IFN, ribavirin, and DFPP had no evidence of HCV recurrence or fibrosing cholestatic hepatitis exacerbation for more than 1 year after liver transplantation [180]. Combination of DFPP and IFN also achieved impressive SVR in difficult-to-treat patients (i.e., relapsed, nonresponder, or HIVcoinfected patients) [181][182][183][184] and may also be safe for the elderly population [185]. However, the approach of apheresis for decreasing HCV viral load requires specialty equipment and possesses potential risk of adverse events (e.g., blood pressure lowering, puncture site hematoma, or infection) [181,185].…”
Section: Therapeutic Apheresis For the Removal Of Hcv Virionsmentioning
confidence: 99%
“…Sugimoto et al [5] reported that double-filtration plasmapheresis plus IFN treatment in nonresponders to pegylated IFN plus RBV combination therapy in patients with a high viral load of hepatitis C genotype 1b achieved SVR in 15% (10/40) of patients, which represents a relatively good result. The significant factors associated with SVR were interleukin-28B major type and a rapid virological response at week 4.…”
mentioning
confidence: 99%